The sense of life and the interpersonal values in university students of the career of Psychology - Arboccó de los Heros, Manuel (2018)
A correlational type research was carried out under a comparative/transversal design. The sample was composed by 277 face-to-face system students enrolled in the 2017 semester in the Psychology School from a private university in Lima, of regular attendance and with consent to participate in the research. These students correspond to three periods of the career: first year of studies (cycles I and II); third year of studies (cycles V and VI) and fifth year of studies (internship I and II – doing their pre professional practices)The research was carried out using Leonard Gordon’s Survey of Interpersonal Values (SIV) and the James Crumbaugh and Leonard Matholick’s Purpose in Life tes, both tests present reliability and validity. It was concluded that there is a significant relationship between the sense of life and interpersonal values in the group of students of the Psychology career.